Deep Vein Thrombosis in Adults with HIV: A Systematic Review and Meta-analysis of Prevalence and Risk Factors - Ismail, Anas; Olawumi, Abdulgafar Lekan; Abdulkadir, Zainab; Kana, Shehu A.; Adamu, Fatima; Yusuf, Aminu A.; Jalo, Rabiu I.; Tsiga-Ahmed, Fatimah I.; Aliyu, Muktar H. (Seminars in Thrombosis and Hemostasis, 2025)
Deep vein thrombosis (DVT) is a preventable yet serious complication among people living with human immunodeficiency virus (PLWH), attributed to hypercoagulability, low CD4+ counts, and antiretroviral therapy. Despite the high burden of human immunodeficiency virus (HIV), data on DVT in this population remain scarce, particularly in high-prevalence regions. This study systematically reviews the prevalence, risk factors, and outcomes of DVT in adults with HIV. Following PRISMA guidelines, we extracted data from 23 studies (180,495 participants) and conducted subgroup analyses based on country, continent, study design, and quality. Heterogeneity and publication bias were assessed statistically. The global DVT prevalence among PLWH was 14%, with Africa reporting the highest prevalence (47%) and Europe the lowest (3%). Kenya exhibited the highest country-specific prevalence (74%), whereas the Netherlands and Denmark had the lowest (2%). Cross-sectional studies reported the highest prevalence (16%). Identified risk factors included hospitalization, opportunistic infections, malignancies, and comorbidities such as hypertension and diabetes. Funnel plot asymmetry indicated potential publication bias and small-study effects. DVT poses a significant health burden among PLWH, particularly in Africa. Given the high prevalence and associated risk factors, integrating DVT prevention and management into HIV care is critical. Targeted interventions should focus on modifiable risk factors and enhanced diagnostic strategies to improve patient outcomes. Future studies should address knowledge gaps and methodological variations to guide better prevention and treatment approaches.
Keywords: deep vein thrombosis; HIV; prevalence; risk factors; pulmonary embolism